Teaching High School Chemistry in the Context of Pharmacology Helps Both Teachers and Students Learn - Schwartz-Bloom, Rochelle D. (2011)
Few studies demonstrate the impact of teaching chemistry embedded in a context that has relevance to high school students. We build upon our prior work showing that pharmacology topics (i.e., drugs), which are inherently interesting to high school students, provide a useful context for teaching chemistry and biology. In those studies, teachers were provided professional development for the Pharmacology Education Partnership (PEP) in an onsite venue (either five-day or one-day workshop). Given financial difficulties to travel, teachers have asked for alternatives for professional development. Thus, we developed the same PEP training workshop using a distance learning (DL) (two-way live video) approach. In this way, 121 chemistry and biology teachers participated in the DL workshops to learn how to incorporate the PEP modules into their teaching. They field-tested the modules over the year in high school chemistry and biology classes. Teacher knowledge of chemistry and biology increased significantly after the workshop and was maintained for at least a year. Their students (N = 2309) demonstrated a significant increase in knowledge of chemistry and biology concepts, with higher scores as the number of modules used increased. The increase in both teacher and student knowledge in these subjects was similar to that found previously when teachers were provided with onsite professional development.